You need to come up with the substitution `y' = (dy)/(dx) = v=> y" = (d^2 y)/(dx^2) = (dv)/(dx) = (dv)/(dy)*(dy)/(dx) = v*(dv)/(dy)`

The problem provides the fact that: `y''-3y^2 = 0 =gt y" = 3y^2` , hence `v*(dv)/(dy) = 3y^2` .

You need to separate the variables hence, multiplying...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to come up with the substitution `y' = (dy)/(dx) = v=> y" = (d^2 y)/(dx^2) = (dv)/(dx) = (dv)/(dy)*(dy)/(dx) = v*(dv)/(dy)`

The problem provides the fact that: `y''-3y^2 = 0 =gt y" = 3y^2` , hence `v*(dv)/(dy) = 3y^2` .

You need to separate the variables hence, multiplying by dy both sides yields:

`vdv = 3y^2 dy`

`` Integrating both sides yields:

`int vdv = int 3y^2 dy =gt (v^2)/2 = 3y^3/3 + c`

`v^2 = 2y^3 + c =gt v = sqrt(2y^3+c)`

At `x = 0 =gt y(0) = 2 and v = y'(0)=4=gt16 = 2*2^3 + c =gt c = 0`

`` `v^2 = 2y^3 =gt v = ysqrt2*sqrty`

`v = dy/dx =gt dy/dx = ysqrt2*sqrty =gt dy/(y^(3/2)) = sqrt2 dx`

Integrating both sides yields:

`int dy/(y^(3/2)) = int sqrt2 dx =gt y^(-3/2 + 1)/(-3/2 + 1) = sqrt2* x + c`

`` `-2/sqrt y = sqrt2*x + c =gt sqrt y = -2/(sqrt2*x + c)`

`y = 4/((sqrt2*x + c)^2)`

The problem provides that y=2 at `x=0 =gt 2 = 4/(c^2) =gt c^2 = 2 =gt c = +-sqrt 2`

Taking `c = -sqrt 2 =gt y = 2/((x-1)^2)`

Taking `c = sqrt 2 =gt y = 2/((x+1)^2)`

**Hence, evaluating solutions to differential equation yields:`y = 2/((x-+1)^2).` **